Elizabethan and Jacobean style - Mowl, Tim. (London : Phaidon Press, 1993)
From the accession of Elizabeth in 1558 to James I's death in 1625, a delayed Renaissance swept England, and prevaded the domestic architecture and interiors of the day. This book shows how classical detail was fused with a Tudor venacular to create a style of enduring popularity
From the accession of Elizabeth in 1558 to James I's death in 1625, a delayed Renaissance swept England, and prevaded the domestic architecture and interiors of the day. This book shows how classical detail was fused with a Tudor venacular to create a style of enduring popularity.
Includes bibliographical references (pages 236-237) and index.
Keywords: Architecture, Elizabethan -- England; Architecture, Jacobean; Decoration and ornament, Elizabethan; Decoration and ornament, Jacobean